Challenges in Education System Affecting Teacher Professional Development in Oman - Amira Al Sulaiman Shabibi; Heikki Silvennoinen (Education Unit of ATINER, 2022)
On international comparisons, the development of Oman’s education system in terms of the increase in educational enrolment rates and in the level of teacher qualifications has been remarkably rapid. Almost 100% access to basic education has been achieved, and almost all students progress onto post-basic education. A report from the World Bank in 2001 described the development of Oman’s education system in the decades 1970-2000 as "unprecedented" and "unparalleled by any other country". However, international assessments on learning outcomes in literacy (PIRLS), and mathematics and sciences (TIMSS) show that Omani students perform very poorly in all three subjects, and that boys’ performance levels are significantly lower than that for girls. The aim of this study is to describe the present-day situation in Omani schooling and the challenges it poses for teacher professional development. The study is based on a meta-analysis of a variety of studies, research reports, articles, and statistics with the aim of presenting a comprehensive picture of the challenges for the development of teaching and learning in Omani schools.